Analysis of Indonesia’s Propensity to Consume Before and During the Pandemic - Fadlli, Muhammad Dzul; Gunawan, Muhammad Indra; Anggriawawn, Robby; Silvida, Fitra Ria; Satarudin, Satarudin (Journal of Finance, Economics and Business, 2024)
The pandemic has hit the country's economic conditions, one of which has affected people's consumption patterns. This study aims to find out and analyze Indonesia’s consumption pattern by looking for how much the marginal propensity to consume (MPC) of the Indonesian people before and during/after the pandemic and to compare their consumption tendencies. The method used in this study is a quantitative method both descriptive and comparative. The use of descriptive quantitative methods to determine and analyze MPC. Meanwhile, to find out the comparison of consumption before the pandemic and at that time used Paired t-test Wilcoxon. This study analyzes Indonesia's consumption by cross-section data from 34 provinces. The result descriptive analysis showed that the propensity to consume before the pandemic was about higher than during the pandemic. Wilcoxon test showed that there is a difference in the propensity to consume before the pandemic and during the pandemic. This research indicates that has been decreasing in the propensity to consume during the pandemic.